Unit Trust With Waqf Feature As Sustainable Investment Conceptual Model In The Era Of Post-covid-19 - Syahnaz Sulaiman; Aznan Hasan; Fuadah Johari; Azrul Azlan Iskandar Mirza (USIM Press, 2024)
Vol. 33 No. S4 (2021): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences